Association between VEGF gene promoter polymorphisms and bladder cancer: An updated meta-analysis. (July 2020) - Chen, Chih-Heng; Ho, Chen-Hsun; Kuan-Hua Huang, Steven; Shen, Cheng-Huang; Wu, Chia-Chang; Wang, Yuan-Hung
Highlights: The influence of VEGF gene promoter polymorphisms on the risk of bladder cancer. VEGF −2578C/A (rs699947) polymorphism was significantly related to bladder cancer. VEGF −460C/T (rs833061) polymorphism was not associated with bladder cancer risk. Significant risk for VEGF −2578C/A polymorphism only in the Asian population. Abstract: Background: Vascular endothelial growth factor (VEGF) is the key regulator of angiogenesis in the development of various cancers. Previous studies have examined the relationship between VEGF gene promoter polymorphisms such as −2578C/A and −460C/T and bladder cancer risk; however, these results are inconclusive. Therefore, we performed this meta-analysis to investigate the association between VEGF gene promoter polymorphisms and bladder cancer risk. Methods: PubMed, Embase, Cochrane Library and Web of Science databases were searched for studies published before September 2018. The methodological quality assessment of included studies was performed based on the Newcastle-Ottawa Quality Scale (NOS). We conducted a systematic review and meta-analysis using both fixed- and random-effect model. Pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to assess the strength of the relationship. In addition, the stability of our analysis was evaluated by heterogeneity, sensitivity, subgroup of ethnicity, and publication bias analysis. Results: We finally included 7 case-control studies with a total of 2412 bladder cancer patients and 3157 cancer-free controls. In Asian population with the VEGF −2578C/A polymorphism, significantly higher bladder cancer risks of 1.55 (95% CI = 1.25–1.93) and 1.53 (95% CI = 1.11–2.10) were found in the heterozygous model (AC vs CC) and the dominant model (AA + AC vs CC), respectively. Though there was no statistical association between VEGF −460C/T polymorphism and bladder cancer, a tendency to higher bladder cancer risk was observed in various genetic models (T vs C; TT vs CC; TC vs CC and TT + TC vs CC). Conclusions: Our findings suggest that VEGF −2578C/A polymorphism might be a risk factor with a modest significance for bladder cancer only in Asian population. Further studies with a larger sample size and other functional polymorphisms are needed to explore the effects of VEGF gene on the risk of bladder cancer.